Assessment of Road Funds in South Asia Region - Guillossou, Jean-Noel (World Bank, Washington, DC, 2012)
Sustaining an adequate level of resources for road maintenance has been a continuous issue worldwide, including in South Asia. Since the late 1990s South Asia has developed different models of Road Funds (RFs), at the national level, or in the case of India at the state and local level, to improve sources of financing for road maintenance and development. The World Bank South Asia transport team has carried out a review of RFs in the region to draw lessons learned from the past experience. The review provides the analytical underpinning for advising governments on how to improve the performance of existing RFs or how to establish new RFs for road maintenance, and for providing guidance to the World Bank for revising its transport sector strategy in relation to road policy reforms in the South Asia region.